Evaluation of Pharmacist-Based Services for Type 2 Diabetes Mellitus in the Indonesian Community Health Centers - Riza Alfian; Yunita Nita; Umi Athiyah (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Diabetes mellitus is a global epidemic that continues to rise, including in Indonesia, and it has significant impacts on public health. The role of pharmacists in providing pharmaceutical care for diabetic patients in community health centers is crucial, yet challenges in its implementation persist. However, in-depth studies on pharmacists' practice experiences in this context are still limited in Indonesia. This study aimed to explore pharmacists' experiences in implementing pharmaceutical care for diabetic patients at community health centers in Indonesia. Methods: The cross-sectional study was conducted in community health centers in South Kalimantan Province, Indonesia. Pharmacists practicing at community health centers were recruited between October and December 2023. The survey was distributed in both paper and online (Google Form) formats. The questionnaire used in the survey focused on the provision of assessment, care plan, and follow-up parameters regarding the medication of diabetic patients. Results: A response rate of 60,3% (n=143) was obtained from pharmacists involved in this survey. Regarding the assessment parameter, the indicator of assessment patient trust was the most dominant implemented by pharmacists (93,7%) compared to other indicators. In terms of the care plan parameter, providing information on medication indications was the most dominant indicator implemented (82,9%). Meanwhile, for the follow-up parameter, the indicator of medication adherence follow-up was the most dominantly implemented by pharmacists (79,1%). Factor analysis revealed that assessment, care plan, and follow-up evaluation each constituted one composite. Conclusion: The pharmaceutical care provided by pharmacists at community health centers for diabetic patients is still suboptimal. The factors that caused the suboptimal implementation of pharmaceutical care were resource limitations, inadequate specialized training for pharmacists, and insufficient support from the healthcare system.